Small Ovarian Teratoma Causes Anti-N-methyl- D-aspartate Encephalitis - Muñoz-Becerra, Valeria; Méndez, Keimari; Cabrera-Martínez, Hilary Ann; García-Irizarry, Adriana N. (Puerto Rico Health Sciences Journal, 2024)
This is the case of a 22-year-old female who arrived at our institution after experiencing refractory insomnia, disorganized behavior, inappropriate laughter, and anorexia. Upon admission, a physical examination revealed mutism, irritability, and visual hallucinations. Infectious, metabolic, and other, alternative, causes for the presenting symptoms were excluded. Brain magnetic resonance imaging and chest and abdominopelvic computed tomography scan results showed no evidence of pathology. Due to there being a high clinical suspicion of paraneoplastic encephalitis, treatment was initiated with intravenous (IV) high-dose steroids and IV immunoglobulins. An endovaginal ultrasound was performed, which revealed a small atypical intraovarian dermoid cyst. The patient’s laboratory tests were positive for anti-N-methyl-D-aspartate antibodies within her cerebrospinal fluid. A laparoscopic right partial salpingectomy and an oophorectomy were performed on day 25, after the symptoms developed further. Histopathology confirmed the presence of a mature teratoma within the right ovary. After surgery, she returned to her baseline mental status, with no further complications.